CERCETAREA RELAŢIEI DINTRE LOCUL DE CONTROL ŞI STILUL APRECIATIV REFLEXIV LA STUDENŢI - USM ADMIN (Moldova State University, 2011)
Contemporary psychology attempts to clarify the efficiency issues in relation with other persons. The research is supporting the leading role of logics and cognitive style, as well as the research supporting the role of affectivity and appreciative reflexive style of the person. Reflexivity was studied in relation to individual impulsivity, which is opposite to the uncontrolled reactions. It is assumed that high self-control correlates with the person reflexivity. In the present research, we intend to clarify the effectiveness of reflexivity in relation to the locus of control.